Acetamido-Propanoic Acid Derived Compounds as Protease Inhibitors to Target Coronaviruses - Kumar, Arun HS; Sharma, Vikram (Biology, Engineering, Medicine and Science Reports)
Background: Coronavirus infection as evolved into a major pandemic and is currently being treated using established antiviral agents developed for other similar viruses. Considering the frequent mutations rate in this virus, novel drugs will be necessary for effective treat- ment in future. Hence this study evaluated the potential of acetamido-propanoic acid derived compounds as viral protease inhibitors. Materials and Methods: Using cheminformatics approach novel acetamido-propanoic acid derived compounds were designed and their binding efficacy against the Coronavirus 2019 (Covid-19) protease was tested using in silico pharma- cology. Results: STGYC compounds had physico-chemical features favourable for developing them for potential clinical use. The binding efficacy of STGYC compounds against Covid-19 protease was similar to that of favipiravir, which currently being reported to be effective in treating coronavirus infection. Conclusion: STGYC compounds shown favourable features to be further evaluated and developed as viral protease inhibitors.
Keywords: Protease inhibitors; SARS-CoV-2; Pandemic; Coronavirus; Covid-19; Antiviral drugs